The effect of peat soil and sandy soil on the growth of Eleutherine palmifolia and arbuscular mycorrhizal diversity - TITIN APUNG ATIKAH; ENY WAHYUNING PURWANTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Atikah TA, Purwanti EW. 2023. The effect of peat soil and sandy soil on the growth of Eleutherine palmifolia and arbuscular mycorrhizal diversity. Biodiversitas 24: 4373-4381. Arbuscular mycorrhizae as root symbionts is capable of inducing plant growth on marginal lands. It has the potential to be used as fertilizer or soil enhancer. Mycorrhizae are commonly found in peat soils endemic to the island of Borneo. Peat soil contains a lot of organic matter needed by mycorrhizae. The development of plant roots also influences the process of mycorrhizal colonization. Apart from functioning as fertilizer, mycorrhizae is associated with Dayak shallot (Eleutherine palmifolia Merr.; syn.: Sisyrinchium palmifolium L.) roots can also overcome fusarium wilt disease. This study aimed to explore the potential of peat soil to support the growth of E. palmifolia 's and to identify mycorrhizal colonization associated with the plant. Two soil types were used for planting E. palmifolia: peat and sand. Parameters observed were plant height, number of leaves, morphospecies and each population of arbuscular mycorrhizae. The plant growth data were tabulated and analyzed with an analysis of variance, and the population of arbuscular mycorrhizae was analyzed for the level of similarity in the structure of species. The results showed that peat soil promoted the growth of E. palmifolia better than sandy soil. The similarity value of mycorrhizal species structure was 28.7%. It means that the structure of mycorrhizal species on peat were differed that on sand media. Mycorrhizae successfully explored from sandy soil were 10 morpho-species with a population of 1.441 spores, while mycorrhizae from peat soil contained 6 morphospecies with a population of 462 spores.